Perancangan Pengalaman Pengguna Aplikasi Manajemen Media Sosial untuk Online Shop berbasis Mobile dengan Metode Design Thinking - Tifanny Rizka Faressi; Ratih Kartika Dewi; Riswan Septriayadi Sianturi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Many people start online shops to fill their spare time during the Covid-19 pandemic. Most online shops use social media as their marketing media. Pioneering online shop businesses are experiencing some problems in terms of social media management. Unmanaged social media may reduce the number of followers and impact sales. Social media management can bring a positive impact on online shop sales. The social media management activities include creating content, scheduling content, and analyzing posts. This study proposes a design solution to solve existing problems by designing a user experience for a social media management application called Socime. The design process is conducted through five stages of design thinking method, from empathize with users to solution design testing. Testing is performed using usability testing, focusing on three aspects: effectiveness, efficiency, and satisfaction. The solution design resulting from this research scored 100% for effectiveness, 0,059 goals/sec for efficiency, and got a SUS score of 90 out of 100 for satisfaction. The Socime design solution received A in grades, Best Imaginable in the adjective rating category, and Acceptable in the acceptability range category based on the SUS score.